Oxidative stress in preterm infants fed a formula containing long-chain polyunsaturated fatty acids (LCPUFA). - Tania Siahanidou; Lazaropoulou, Christina; Michalakakou, Kelly; Papassotiriou, Ioannis; Bacoula, Chrysa; Mandyla, Helen (Am J Perinatol, 2007)
{Our study examined if dietary long-chain polyunsaturated fatty acids (LCPUFA) have an impact on oxidative stress in preterm infants. Serum malonyldialdehyde (MDA), total peroxide concentrations, and total antioxidant capacity were determined at mean (standard deviation [SD]) 34.7 (10.9) days of life in 104 healthy preterm infants (gestational age, 32.6 [2.9] weeks; birthweight; 1605 [285] g) who were randomly assigned to be fed since birth either a formula containing LCPUFA (arachidonic and docosahexaenoic) (group A
Keywords: Arachidonic Acid; Docosahexaenoic Acids; Female; Humans; Infant; Infant Formula; Lipid Peroxidation; Male; Malondialdehyde; Newborn; Oxidative Stress; Premature; Prospective Studies